Queer - Getsy, David (Whitechapel Gallery ; The MIT Press, 2016)
"Rather than a book of queer theory for artists, this is a book of artists' queer tactics and infectious concepts. In the first such anthology to be centred on artists' writings, numerous conversations about queer practice are brought together from diverse individual, social and cultural contexts. Together these texts describe and examine the ways in which artists have used the concept of queer as a site of political and institutional critique, as a framework to develop new families and histories, as a spur to action, and as a basis from which to declare inassimilable difference"–Back cover.
Keywords: LGBTQIA2+; approches et analyses; arts; arts visuels et médiatiques; cours; critique institutionelle; critique politique; discipline; har4600; identités LGBTQIA2+; intersectionnalité; militance; pratique artistique; premier cycle; queer; thématiques; écrits d'artiste

Otherwise: imagining queer feminist art histories - Jones, Amelia; Silver, Erin (Manchester University Press, 2016)
Otherwise: Imagining queer feminist art histories" is the first publication to address queer feminist politics, methods and theories in relation to the visual arts, including new media, installation and performance art. Despite the crucial contribution of considerations of 'queer' to feminism in other disciplines of the humanities, and the strong impact of feminist art history on queer visual theory, a visible and influential queer feminist art history has remained elusive. This book fills the gap by offering a range of essays by key North American and European scholars, both emerging and renowned, who address the historiographic and political questions arising from the relationship between art history and queer theory in order to help map exclusions and to offer models of a new queer feminist art historical or curatorial approach.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; europe; har4600; histoire de l'art; identités LGBTQIA2+; installation; performance; premier cycle; queer; régions géographiques; thématiques; transféminisme

Recomposing the self: Joyful shame in Dorothy Allison's "Bastard Out of Carolina" - Walerstein, Rachel (Mosaic: An Interdisciplinary Critical Journal, 2016)
Dorothy Allison’s Bastard Out of Carolina is typically read as representative of the negative effects of trauma. This essay suggests that one’s shame can be used to recompose the shamed self, enabling one to (re)connect with others.
Keywords: approches et analyses; arts; discipline; honte; personnes lesbiennes; queer; ressource en ligne; émotions; études littéraires